Sekufu Dalam Perkawinan Perspektif Hukum Islam - annisa; Fatimah; Devani; Syifa; Khairul (Tabayyun : Journal Of Islamic Studies, 2024)
Marriage is very important in human life to achieve happiness, calm and affection, harmony and balance are needed. This harmony and balance is what is meant by Kufu. The purpose of Kufu in islam is none other than to maintain the strength of offspring, as well as to unsure the continuity of marriage. This research aims to determine the saquelae of marriage from an Islamic perspective.